Stabilitas Ekstrak Pewarna Alami Bunga Kenop (Gomphrena globosa L.) selama Penyimpanan pada Perlakuan Intensitas Cahaya - Parnawan, Gusti Ayu Mas Alstonia; Wartini, Ni Made; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 4 (2021): DesemberDO - 10.24843/JRMA.2021.v09.i04.p04, 2021)
The betacyanin content of the globe amaranth extract is unstable on storage due to temperature, pH, light intensity and oxidizing factors. The objectives of this study were (1) to know the effect light intensity on the stability of the globe amaranth extract during storage, and (2) to determine the light intensity treatment that can  maintain the best stability of the globe amaranth extract during storage. This study used a simple completely randomized design with light intensity treatment consisting of 5 levels, namely 200 lumens, 350 lumens, 540 lumens. 720 lumens and 1055 lumens. Each treatment was carried out 3 times so that there were 15 experimental units.  The results showed that the light intensity treatment had an effect on the stability of the  betacyanin content of the globe amaranth extract during storage. Light intensity treatment of 200 lumens is a treatment that can maintain the stability of the globe amaranth extract with the smallest percentage reduction in total betacyanin content of 46.07% for 4 weeks of storage. Keywords: globe amaranth extract, betacyanin, light intensity, stability